Artefakty i różne style ich doświadczania w kulturze konsumpcji - Witosz, Bożena (Stylistyka, 2020)
The author adopts a broad definition of an artifact as an artificial creation that is created by man. Real and virtual objects, both artistic and utilitarian, are housed in the collection. This article aims to identify some trends, which are often contradictory, in the relationship between people and things that crystallized in the era of postmodern consumerism. These trends do not fall within the mainstream. Generally speaking, they are an expression of social discord on the destruction of items. The author addresses several topics: a) the inclination to save things that can be observed in contemporary literature. Images of trash, abandoned industrial sites and landfills of civilization induce nostalgia for the styles of the past. They are also a part of the identity of the individual; b) recycling and the recovery of specific things, which is visible both in the Internet space (also in the area of net-art) as well as in real life. This is an indication that in a civilization of overproduction, the repeated use of things may be a cultural pattern; c) as a result, the “de-aestheticization of art” and “aestheticization of everyday life” has blurred the line between art and utility and is the cause of the semantic and axiological instability of things. Differences in the perception of artifacts can result in serious conflicts that sometimes arise in the public space.